NECESIDAD DE TRATAMIENTO BUCAL Y CALIDAD DE VIDA EN EL ADULTO MAYOR (2013)
Objective: to assess the oral treatment needs and its effect on oral health related quality of life in older adults.Methods: a cross sectional study in six elderly nursing home care from the city of Floridablanca, Santander (Colombia) was done. Treatment needs were established according to the World Health Organization (WHO) and the oral health related quality of life according to the Spanish version of the Geriatric Oral Health Assessment Index (GOHAI). Measures of central tendency and dispersion for quantitative variables and proportions for qualitative ones were obtained. Chi2 test or Fisher’s Exact was used as appropriate. A value of p ≤ 0.05 was considered significant.Results: of the 111 seniors surveyed, 62.2% needed special treatment for systemic diseases. 13.5% required intervention by clinical management while 37.8% of the population needed special treatment for salivary flow. 44.4 % required deep scaling and root planning and oral hygiene education was needed in 86.5%. The frequencies of self-perception and oral health related quality of life did not show any statistically significant association.Conclusions: the three main treatment needs in their order were oral hygiene education, special treatment for systemic disease and periodontal treatment. Treatment needs were more important in patients with low quality of life scores according GOHAI but no statistically significant difference was observed.